Diminished bactericidal capacity for group B streptococci of neutrophils from children with chronic granulomatous disease. - Stroobant, J (1983)
The bactericidal capacity of neutrophils from healthy adults, male children with chronic granulomatous disease, and obligate heterozygote mothers for type Ic group B streptococci was assessed, using a fluorochrome microassay. Neutrophils from patients with chronic granulomatous disease had impaired bactericidal capacity for group B streptococci when compared with adults (P less than 0.01). Carriers demonstrated intermediate killing capacity.